Clinical Advantages and Limitations of Monolithic Zirconia Restorations Full Arch Implant Supported Reconstruction: Case Series - Joao Carames; Loana Tovar Suinaga; Yung Cheng Paul Yu; Alejandro Pérez; Mary Kang (International Journal of Dentistry)
Purpose. The purpose of this retrospective case series is to evaluate the clinical advantages and limitations of monolithic zirconia restorations for full arch implant supported restorations and report the rate of complications up to 2 years after insertion. Materials and Methods. Fourteen patients received implant placement for monolithic zirconia full arch reconstructions. Four implants were placed in seven arches, eleven arches received six implants, two arches received seven implants, two arches received eight implants, and one arch received nine implants. Results. No implant failures or complications were reported for an implant survival rate of 100% with follow-up ranging from 3 to 24 months. Conclusions. Monolithic zirconia CAD-/CAM-milled framework restorations are a treatment option for full arch restorations over implants, showing a 96% success rate in the present study. Some of the benefits are accuracy, reduced veneering porcelain, and minimal occlusal adjustments. The outcome of the present study showed high success in function, aesthetics, phonetics, and high patient satisfaction.